Pharmacodynamic Profiling of Antimicrobials against Gram-negative Respiratory Isolates from Canadian Hospitals - Rebecca A. Keel; George G. Zhanel; Sheryl Zelenitsky; David P. Nicolau (Canadian Journal of Infectious Diseases and Medical Microbiology)
The objective of this study was to assess the profile of a variety of dosing regimens for common intravenous antibiotics against contemporary Enterobacter cloacae, Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa isolates collected in Canada during 2009, using pharmacodynamic modelling techniques. Monte Carlo simulation was conducted for standard and/or prolonged infusion regimens of cefepime, ceftazidime, ceftriaxone, ciprofloxacin, doripenem, ertapenem, meropenem and piperacillin/tazobactam. The cumulative fraction of response (CFR) was calculated using bactericidal targets for each regimen against each species. All cefepime, doripenem, ertapenem and meropenem regimens achieved optimal exposures against Enterobacteriaceae, whereas target attainment was organism and dose dependent for the other agents. These results support that the currently recommended antimicrobial dosing regimens generally attain acceptable exposures to achieve the requisite pharmacodynamic targets against the Enterobacteriaceae species; however, they fall short of obtaining optimal bactericidal exposures against P aeruginosa.